Potensi Bisnis Rumah Sakit Dalam Medical Tourism - Neng Sari Rubiyanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The hospital business is the main subject in carrying out medical tourism. For this reason, the hospital business has the potential to support the development of medical tourism. This research is about the potential of the hospital business in medical tourism with the problem of what is meant by medical tourism? and How is the potential of the hospital business in Indonesia in contributing to medical tourism? This research is normative juridical research using secondary data collected by library research and document study techniques which were analyzed qualitatively. Medical tourism or medical tourism is a trip out of town or from abroad to obtain examinations, medical procedures, and/or other medical examinations at a hospital. Based on the juridical understanding of medical tourism, hospitals are the main component in medical tourism. The development of medical tourism provides great potential for the hospital business in Indonesia to contribute to the economy in the form of state financial income. This is because Indonesia is a country with quite rapid tourism development with adequate quality hospitals in providing health services. For this reason, the government issued Permenkes No. 76 of 2015 concerning Medical Tourism Services in developing the hospital business so that it can contribute to medical tourism. The development of medical tourism provides great potential for the hospital business in Indonesia to contribute to the economy in the form of state financial income. This is because Indonesia is a country with quite rapid tourism development with adequate quality hospitals in providing health services. For this reason, the government issued Permenkes No. 76 of 2015 concerning Medical Tourism Services in developing the hospital business so that it can contribute to medical tourism. The development of medical tourism provides great potential for the hospital business in Indonesia to contribute to the economy in the form of state financial income. This is because Indonesia is a country with quite rapid tourism development with adequate quality hospitals in providing health services. For this reason, the government issued Permenkes No. 76 of 2015 concerning Medical Tourism Services in developing the hospital business so that it can contribute to medical tourism.